Studi Variabilitas Produktivitas Primer Bersih Serta Hubungannya dengan El-Nino Southern Oscillasion (ENSO) dan Indian Ocean Dipole (IOD) di Laut Banda Berdasarkan Data Satelit Aqua MODIS - Ni Luh Novita Aryanti; I Gede Hendrawan; Yulianto Suteja (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Banda Sea is one of the waters had rich of fish catch. The high catch of fish was related with primary productivity of these waters. Net Primary productivity in the Banda Sea was related with some oceanographic factors such as current, ARLINDO, upwelling and downwelling. The oceanographic factors are influenced by ENSO and IOD. The aim of this research to explained the variability of net primary productivity in Banda Sea and its relation with oceanography factor such as ENSO and monsoon. Data that used in this research were data from MODIS satellite and for analysis of net primary productivity data used Vertically Generalized Production Model (VGPM). The relation of net primary productivity with ENSO and IOD can used pearson correlation method. The result of net primary productivity value in Banda Sea was about 100 gCm-2day-1 - 1200 gCm-2day-1, with the highest apex net primary productivity in August precisely in the east season. The high value of net primary productivity due to upwelling in the season. The value of net primary productivity in west season was decreased. This condition caused by the downwelling of the season. The region with the highest net primary productivity value was the northeast of Banda Sea and the region with lowest net primary productivity value was the western of Banda Sea. The relationship between ENSO with net primary productivity in Banda Sea classified in medium correlation with value 0,556, while relationship between IOD and net primary productivity classified in weak correlation with value 0,23.